2021
DOI: 10.1007/s11356-021-15979-9
|View full text |Cite
|
Sign up to set email alerts
|

Study on complex dynamics for the waste electrical and electronic equipment recycling activities oligarchs closed-loop supply chain

Abstract: Nowadays, with more and more WEEE (Waste Electrical and Electronic Equipment) being abandoned, WEEE recycling activities are increasingly popular. In this paper, we build a closed-loop supply chain model and focus on the recycling behaviors of the members in this supply chain, which contains two manufacturers, the retailer and the consumer. In the reverse chain, we set up dual channels and design two recycling methods: sell-back method and trade-in method. We use classical backward induction to run the model. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…They found that government intervention maximizes social welfare. Zhu et al [34,35] established a closed-loop supply chain model of used electrical appliances, considering two recycling methods: resale method and new trade-in method. It is found that the speed of manufacturer's decision adjustment has significant influence on the stability of the model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that government intervention maximizes social welfare. Zhu et al [34,35] established a closed-loop supply chain model of used electrical appliances, considering two recycling methods: resale method and new trade-in method. It is found that the speed of manufacturer's decision adjustment has significant influence on the stability of the model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, based on studies on environmental protection policies, Bao et al fnd that the prices of battery electric vehicles are more dependent on government subsidy than fuel vehicles [7]. It is also approved that government subsidies and carbon emission reduction have an efective infuence on the development of electric vehicles [8][9][10]. However, policies of government subsidies can also have a negative efect, for instance, on the supply chain system's stability [11].…”
Section: Theoretical and Institutional Backgroundmentioning
confidence: 99%
“…How can we combine collection and remanufacturing organically to achieve a circular economy and environmental protection based on environmental responsibility and interests? Many companies and numerous scholars are focusing on this problem in the closed-loop supply chain (CLSC) in the literature related to the collection and remanufacturing of WEEE [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%